Visual flow does not alter muscle activity during treadmill walking or running - Jensen, R. L.; Zueger, L. A.; Sellman, B. J.; Scatena, P.; Stephenson, M. L. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The current study examined the effect of visual flow (patterns of visual movement of surroundings) on muscle activity during treadmill walking and running. Participants (n=14 walked (1 -39 m-s4) and ran (2.78 msl) in visual flow and control conditions. Activity of the vastus medalis (VM), biceps fernoris (BF), gluteus maximus (GM ), gastrocnemius (GA), tibialis anterior (TA), erector spinae (ES), mtus abdominis (RA), and C4 paraspinal (C4) were assessed via electromyography (EMG) during each condition. Repeated Measures ANOVA revealed EMG differences (p < 0.05) between walking and running for RA, VM, GM, and BF. There were no differences in speeds for the other muscles, or across the visual conditions for any of the muscles. Visual flow does not alter muscle activity during walking or running